Flood Incidences as Public Health Challenge in Katsina State, Northern Nigeria - Suleiman Iguda Ladan; Mohammed Babatsu Mayaki (Indonesian Journal of Earth Sciences, 2023)
Flood incidences are one of the major environmental hazards that occur yearly in different parts of the world.  The year 2022 has witnessed series of catastrophic floods not experienced in recent times in parts of countries such as Afghanistan, Bangladesh, Italy, Pakistan, Niger Republic, Pakistan, South Africa and United State of America.  Nigeria like other developing countries in the continent of Africa has also experienced this kind of floods incidences.  This paper examines flood incidences as a public health challenge in Katsina state northern Nigeria.  Data for the study was generated from a semi-structured questionnaire administered on 100 students.  The students are those studying National Diploma in Environmental Health Technology at Hassan Usman Katsina Polytechnic, Katsina, Katsina State.  Data on annual flood incidences from 2018 – 2022 was collected from the Katsina State Emergency Management Agency (SEMA) including discussions with the Directors of Information and Search and Rescue.  The results have shown that flood incidences within the period under study have become a public health challenge resulting to loss of lives, injuries to victims, destruction of houses and creation of displaced persons among others.  These are happening despite the efforts of Katsina State Government to tackle the challenges posed by the floods to public health.  It is therefore recommended that on-going flood control projects should continue and more efforts on safeguarding public health from flood incidences be pursued.